Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode RGEC - Novia Dwi Astari; Dadang Hermawan; Rosma Pakpahan (Indonesian Journal of Economics and Management, 2021)
This study aims to assess the bank health level of PT Bank Mandiri (Persero), Tbk. In 2016-2020 using the RGEC method, which is viewed from the factors of Risk Profile, Good Corporate Governance, Earnings, and Capital. The financial ratios used in assessing the health level of bank include: risk profile using 2 (two) ratios, namely NPL (Non Performing Loan) for the credit risk aspect and LDR (Loan to Deposit Ratio) for the liquidity aspect. Earnings using 2 (two) ratios, namely ROA (Return On Assets) and NIM (Net Interest Margin). Capital uses the CAR (Capital Adequacy Ratio). As for the GCG factor assessment using the results of the self-assessment that has been carried out by Bank Mandiri. The results of this study indicate that Bank Mandiri’s Health Level in 2016-2020 received the predicate “Very Healthy”.